Cloning and Expression of the Gene for the Na(+)-Coupled Serine Transporter from Escherichia coli and Characteristics of the Transporter - Ogawa, Wakano (American Society for Microbiology, 1998)
We cloned a gene (sstT) for the Na(+)/serine symporter from the chromosome of Escherichia coli by using a low-copy-number vector and sequenced it. According to the deduced amino acid sequence, the transporter (SstT) consists of 414 amino acid residues. Hydropathy analysis suggested that the SstT protein possesses 9, instead of 12, hydrophobic domains.